Immigrant perceptions of the police: Theoretical explanations - Wu, Yuning (International journal of police science & management, 2017)
A notable limitation among existing studies on immigrant perceptions of the police is the lack of a guiding theoretical framework in data analyses. This article delineates the theoretical perspectives that may explain group differential views on the police between immigrants and non-immigrants, and among immigrant groups. In particular, we formulate a new conceptual framework for classifying these theories. Theories are first organized by the two sources of influence that immigrant attitudes toward the police are subject to: universal factors that tend to shape all residents’ attitudes toward the police, and group-specific factors that apply only to foreign-born individuals. Then within both universal and immigrant-specific factors, there are four subcategories of demographic, experiential, structural, and attitudinal variables. Recommendations for future research are included.